ASSESSMENT OF ARTESUNATE TOXICITY ON RENAL TISSUE OF MALE ALBINO MICE - D. K. RAJPUT,; N. MOID,; P. B. PATEL,; L. B. GEORGE,; K. R. DESAI,; H. N. HIGHLAND, (The Bioscan, 2013)
About 500 million people suffer from malaria leading to death in 2 to 3 million cases. Acute renal failure occurs as a complication of P. falciparum malaria in less than 1% of cases, but the mortality in these cases may be upto 45%. Artesunate is an antimalarial drug used for the treatment of falciparum malaria in regions of malaria endemicity. The effect of varying doses of artesunate on functional indices of mice kidney was investigated. Oral doses of 150 mg/kg.b.wt and 300 mg/kg.b.wt of artesunate were administered for a period of 21 and 45 days. Effects were observed on some biochemical parameters like protein, cholesterol, LPO (TBARS), SOD, GSH, GPx, G-Rx, GST and histology of concerned tissue using standard methods. Gravimetric indices were also recorded. The results of investigation revealed lowered level of protein and elevated cholesterol content in the test tissue after 21 and 45 days of administration of both low and high dose of Artesunate. Similarly, oxidative parameters SOD, GSH, G-Px, G-Rx were found to be decreased and LPO (TBARS) and GST were found to be increased as compared to control animals after the termination of experiment. The histological findings after H&E staining showed interstitial lymphoplasmacytic nephritis and necrosis in the epithelial cells of the renal tubules at 21 days post treatment. Cytology of renal cells was also altered compared to control slides after 45 days post treatment. Treatment with high dose of Artesunate showed hemorrhage within interstitial tissue and proliferation of epithelial cell lining of renal tubules followed by necrotic glomerular tufts. Thus, obtained results clearly indicate the adverse effects of artesunate administration on functional capacities of the kidney.